Diplomatic relations between the eastern Roman empire and the "barbarian" successor states, 527–565. Issue 11 (28th October 2018) - Sarantis, Alexander
Abstract: Diplomatic relations between the eastern Roman emperor, Justinian, and "barbarian" Ostrogothic, Vandal, Visigothic, and Frankish successor states in Italy, Africa, Spain, and Gaul, were framed by competing claims to Romanitas during a period often viewed as a crossroads between Antiquity and the Middle Ages. Modern works examining these relations and the wars which resulted disagree as to whether the ruling elites of the successor states were politically "integrated" into Roman society or were barbarian interlopers, awkwardly trying to balance the interests of Germanic military aristocracies and native Roman senatorial and ecclesiastical elites. They thus reflect competing eastern Roman and western ideologies in the aftermath of the political disintegration of the western Roman empire in the fifth century.